A Comparative Study on the Clinical Efficacy of Modified Circumcision and Two Other Types of Circumcision - Su, Quanxin; Gao, Shenglin; Chen, Jiasheng; Lu, Chao; Mao, Weijiang; Wu, Xingyu; Zhang, Lifeng; Zuo, Li (Urology Journal, 2020)
Purpose: To compare the clinical effects of three methods of circumcision: modified circumcision, traditional circumcision, and disposable suturing device circumcision. Materials and Methods: Male patients (n = 241) with redundant prepuce and/or phimosis were included in a clinical trial from January 2019 to March 2020. Patients were divided into 3 groups based on the surgical method: group A, traditional circumcision (n = 79); group B, modified circumcision (n = 80); and group C, disposable suturing device circumcision (n = 82). Results: The operation times in groups A, B, and C were 25.2 ± 3.3 min, 10.2 ± 2.7 min, and 6.7 ± 1.4 min, respectively. The volumes of intraoperative blood loss in groups A, B, and C were 12.7 ± 2.3 mL, 8.1 ± 3.4 mL, and 2.2 ± 0.8 mL, respectively (P < 0.05). Groups A and B were superior to group C in terms of the 6-h postoperative visual analog scale score and appearance satisfaction (P < 0.05). There were no obvious differences in the 7-day postoperative pain score and total healing time (P > 0.05). The operating expenses in groups A and B were lower than that in group C (P < 0.05). Conclusion: Modified circumcision, with its advantages of shorter operation time, less blood loss and pain, lower cost, and better postoperative penile appearance, is easily accepted by patients and deserves wide clinical application.